FEATURES OF THE FORMATION AND DEVELOPMENT OF THE BODY OF SELF-GOVERNMENT OF LAWYERS - V. Davlyatov (European Science Publishing, 2025)
The article analyzes the specific features of the formation and development of a self-governing body of lawyers. Scientific research and study of the genesis of the development of the organizational and legal foundations of the institute of advocacy in our country and its specific features are of great importance in improving the organizational and legal foundations of the institute of advocacy.
Keywords: Legal aid, bar association, presidium authority, public associations, Bar Association.